2022
DOI: 10.1007/s00256-022-04155-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of virtual interviews on the musculoskeletal radiology fellowship match

Abstract: Objective Resulting from the COVID-19 pandemic, a virtual interview format was adopted in lieu of in-person interviews for fellowship recruitment. The purpose of this study is to analyze the potential effect that virtual interviews have on musculoskeletal radiology fellowship match results and collect opinions of the process. Materials and methods An anonymous survey was sent to 87 listed US-based musculoskeletal radiology fellowship directors, who were asked for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our study found that 61% of PCCM PDs would like to conduct VIs in the future, even under usual circumstances. In our study, 77% of the PCCM PDs agreed that VIs allowed them to represent their programs ( 11 ), 64% would prefer VIs because they reduce financial burden ( 15 ), and 59% agreed that the number of applicants increased because of the VI format ( 16 ). This is in alignment with previous survey studies.…”
Section: Discussionmentioning
confidence: 68%
“…Our study found that 61% of PCCM PDs would like to conduct VIs in the future, even under usual circumstances. In our study, 77% of the PCCM PDs agreed that VIs allowed them to represent their programs ( 11 ), 64% would prefer VIs because they reduce financial burden ( 15 ), and 59% agreed that the number of applicants increased because of the VI format ( 16 ). This is in alignment with previous survey studies.…”
Section: Discussionmentioning
confidence: 68%